Da Puṣhtano mujāhide - Rishtīn, Ṣiddīq Allāh (Da Puṣhtūnistān da khaprawano lar ;, 1952)
On the role played by the Pathans in various freedom movements of Afghanistan and India; mid-18th century - mid 20th century.